Central Regulation of PCOS: Abnormal Neuronal-Reproductive-Metabolic Circuits in PCOS Pathophysiology - Liao, Baoying; Qiao, Jie; Pang, Yanli (Frontiers in Endocrinology, 2021)
Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disease, PCOS patients are characterized by hyperandrogenemia, anovulation and metabolic dysfunction. hypothalamus-pituitary-ovary axis imbalance is considered as an important pathophysiology underlying PCOS, indicating that central modulation, especially the abnormal activation of hypothalamic gonadotropin-releasing hormone (GnRH) neurons plays a vital role in PCOS development. Increased GnRH pulse frequency can promote luteinizing hormone (LH) secretion, leading to ovarian dysfunction and abnormal sex steroids synthesis. By contrast, peripheral sex steroids can modulate the action of GnRH neurons through a feedback effect, which is impaired in PCOS, thus forming a vicious cycle. Additionally, hypothalamic GnRH neurons not only serve as the final output pathway of central control of reproductive axis, but also as the central connection point where reproductive function and metabolic state inter-regulate with each other. Metabolic factors, such as insulin resistance and obesity in PCOS patients can regulate GnRH neurons activity, and ultimately regulate reproductive function. Besides, gut hormone act on both brain and peripheral organs to modify metabolic state. Intestinal flora disturbance is also related to many metabolic diseases and has been reported to play an essential part in PCOS development. This review concludes the mechanism of central modulation and the interaction between neuroendocrine factors and reproductive or metabolic disorders in PCOS development. Furthermore, the role of gut microenvironment as an important part involved in the abnormal neuronal-reproductive-metabolic circuits that contributes to PCOS is discussed, thus offering possible central and peripheral therapeutic targets for PCOS patients.